2018
DOI: 10.1177/1090198118788610
|View full text |Cite
|
Sign up to set email alerts
|

OMG U #Cyberbully! An Exploration of Public Discourse About Cyberbullying on Twitter

Abstract: Cyberbullying, defined as bullying that takes place using technology, includes similar tactics found in traditional bullying as well as unique approaches such as viral repetition. Nationally, prevalence rates for cyberbullying range from 10% to as high as 40% of school-aged children, depending on the definition and measurement tool applied. The current study examines public tweets with keywords and hashtags related to cyberbullying posted during May 2016, using both human evaluation and computer examination to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 19 publications
2
19
0
Order By: Relevance
“…Twitter has become a valuable source of information to explore peoples' behaviors and viewpoints about various public health and social issues (Karami, Dahl, Turner‐McGrievy, Kharrazi, & Shaw Jr, ). However, few studies (e.g., McHugh, Saperstein, & Gold, ) have used Twitter as a data source to explore people's viewpoints on cyberbullying. The present study will contribute to the literature by applying a textual analytics method to reveal people's cognition and perception about cyberbullying.…”
Section: Introductionmentioning
confidence: 99%
“…Twitter has become a valuable source of information to explore peoples' behaviors and viewpoints about various public health and social issues (Karami, Dahl, Turner‐McGrievy, Kharrazi, & Shaw Jr, ). However, few studies (e.g., McHugh, Saperstein, & Gold, ) have used Twitter as a data source to explore people's viewpoints on cyberbullying. The present study will contribute to the literature by applying a textual analytics method to reveal people's cognition and perception about cyberbullying.…”
Section: Introductionmentioning
confidence: 99%
“…Although GSN apps are widely used by the general population, public health practitioners and educators are just beginning to use this resource as a tool for research, education, and sharing information [29]. Our findings suggest that GSN apps can be used to reflect the behavior characteristics of gay men and identify individuals at risk of casual sex and HIV.…”
Section: Discussionmentioning
confidence: 97%
“…Findings from Pyzalski ( 2012 ) suggest that in addition to bullying targets known offline, online spaces also allow for the cyberbullying of strangers, vulnerable individuals (for example, the homeless or alcoholics), celebrities, and specific groups (for example, fans of a certain band or football team). A qualitative analysis of cyberbullying-related tweets found that more than half (56.3%) included individuals known to the users, 29% had no clear subject, and 15% was referring to a celebrity or someone not personally known (McHugh et al, 2019 ).…”
Section: Literature Reviewmentioning
confidence: 99%